Brain development is impaired in c-fos -/- mice - Velazquez, Fabiola Noelia (2015)
c-Fos is a proto-oncogene involved in diverse cellular functions. Its deregulation has been associated to abnormal development and oncogenic progression. c-fos-/- mice are viable but present a reduction in their body weight and brain size. We examined the importance of c-Fos during neocortex development at 13.5, 14.5 and 16.5 days of gestation. At E14.5, neocortex thickness, apoptosis, mitosis and expression of markers along the different stages of Neural Stem Progenitor Cells (NSPCs) differentiation in c-fos-/- and wild-type mice were analyzed. A ~15% reduction in the neocortex thickness of c-fos-/- embryos was observed which correlates with a decrease in the number of differentiated cells and an increase in apoptosis at the ventricular zone. No difference in mitosis rate was observed, although the mitotic angle was predominantly vertical in c-fos-/- embryos, suggesting a reduced trend of NSPCs to differentiate. At E13.5, changes in differentiation markers start to be apparent and are still clearly observed at E16.5. A tendency of more AP-1/DNA complexes present in nuclear extracts of cerebral cortex from c-fos-/- embryos with no differences in the lipid synthesis activity was found. These results suggest that c-Fos is involved in the normal development of NSPCs by means of its AP-1 activity.